Aligning economic and social value creation through pay-what-you-want pricing. Issue 1 (2nd January 2016) - Mendoza-Abarca, Karla I.; Mellema, Hillary N.
Abstract: The main objective of social ventures is the creation of social value. However, these organizations must also generate and appropriate economic value to fund their social value-creating activities. Mechanisms that enable the alignment of these seemingly contradicting goals are necessary. The authors propose that a participative pricing mechanism known as pay-what-you-want (PWYW) is capable of aligning a venture's economic and social value creation goals. This mechanism allows customers to determine the price they are willing and able to pay. The authors explain that this mechanism enables social ventures to generate social value through their commercial activities by serving more beneficiaries in need, reducing the stigma of receiving help, allowing non-disadvantaged customers to show support for the social venture, and aligning commercial activities with the social mission, all while ensuring that sufficient economic value is captured to sustain operations.